PENGATURAN PARAMETER HIDROLOGI PADA DAS CIKAPUNDUNG UNTUK ANALISA DEBIT BANJIR - Sandi Yudha Pratama, - (2019)
Sungai Cikapundung merupakan anak Sungai Citarum yang mempunyai hulu terletak di daerah Cigulung, Maribaya, Kabupaten Bandung Barat dan bermuara di Sungai Citarum daerah Bale Endah, Kabupaten Bandung. Sungai Cikapundung mempunyai pos duga air salah satunya di daerah Cikapundung-Gandok. Pos duga air ini menghasilkan data berupa tinggi muka air di Sungai Cikapundung, kemudian dapat digunakan untuk perhitungan debit banjir. Perhitungan debit banjir juga dapat dihasilkan dengan model hidrograf satuan sintetik yang menghasilkan debit banjir rencana. Perhitungan debit banjir rencana dapat dianalisa menggunakan metode Soil Conservation Service (SCS), HSS Snyder, HSS Gamma I, HSS Nakayasu, HSS ITB-1 dan HSS ITB-2. Penelitian ini dianalisa menggunakan metode deskriptif kuantitatif. Perhitungan debit banjir rencana di Sungai Cikapundung dengan menggunakan metode Soil Conservation Service didapat debit banjir puncak sebesar 37.118 m³/s, dengan HSS Snyder didapat debit banjir puncak sebesar 8.407 m³/s, dengan HSS Gamma I didapat debit banjir puncak sebesar 4.998 m³/s, dengan HSS Nakayasu didapat debit banjir puncak sebesar 4.911 m³/s, dengan HSS ITB-1 didapat debit banjir puncak sebesar 3.509 m³/s, dan dengan HSS ITB-2 didapat debit banjir puncak sebesar 14.554 m³/s. Pada perhitungan debit banjir rencana pada DAS Cikapundung yang mendekati debit eksisting adalah HSS Snyder. Setelah perhitungan semua metode hidrograf satuan sintetik dan dibandingkan dengan hidrograf debit eksisting Sungai Cikapundung, dilakukannya optimasi parameter di tiap-tiap metode HSS. Optimasi parameter pada HSS metode SCS adalah nilai CN = 43, dengan menghasilkan debit puncak sebesar 28.55 m³/s, optimasi parameter pada HSS metode Snyder adalah nilai Ct = 1.25 dan Cp = 1.15, dengan menghasilkan debit puncak sebesar 15.37 m³/s, optimasi parameter pada HSS Nakayasu adalah nilai α = 1.5 dengan menghasilkan debit puncak sebesar 7.35 m³/s, optimasi parameter pada HSS ITB-1 adalah nilai Ct = 0.75 dan Cp = 1.4 dengan menghasilkan debit puncak sebesar 4.51 m³/s, kemudian optimasi parameter pada HSS ITB-2 adalah nilai Ct = 3 dan Cp = 1.4 dengan menghasilkan debit puncak sebesar 8.42 m³/s.;--Cikapundung River is a tributary of the Citarum River which has an upstream area located in Cigulung, Maribaya, West Bandung Regency and empties into the Citarum River Bale Endah area, Bandung Regency. Cikapundung River has one of the alleged water posts in the Cikapundung-Gandok area. This estimated water post produced data in the form of water level in the Cikapundung River, which could then be used to calculate flood discharge. Calculation of flood discharge can also be generated with a synthetic unit hydrograph model that generates a planned flood discharge. Calculation of flood plan can be analyzed using the Soil Conservation Service (SCS), SUH Snyder, SUH Gamma I, SUH Nakayasu, SUH ITB-1 and SUH ITB-2. This research was analyzed using quantitative descriptive methods. Calculation of planned flood discharge in Cikapundung River using the Soil Conservation Service method obtained peak flood discharge of 37,118 m³ / s, with SUH Snyder obtained peak flood discharge of 8,407 m³ / s, with SUH Gamma I obtained peak flood discharge of 4,998 m³ / s, with SUH Nakayasu obtained peak flood discharge of 4,911 m³ / s, with SUH ITB-1 obtained peak flood discharge of 3,509 m³ / s, and with SUH ITB-2 obtained peak flood discharge of 14,554 m³ / s. In the calculation of the planned flood discharge in the Cikapundung watershed which approaches the existing discharge is SUH Snyder. After calculating all the synthetic unit hydrograph methods and comparing them with the existing discharge hydrograph of the Cikapundung River, parameters were optimized for each SUH method. Parameter optimization on SUH method of SCS is CN = 43, resulting in peak discharge of 28.55 m³ / s, parameter optimization on SUH Snyder method is Ct = 1.25 and Cp = 1.15, by producing peak discharge of 15.37 m³ / s, parameter optimization the SUH Nakayasu is a value of α = 1.5 to produce a peak discharge of 7.35 m³ / s, parameter optimization on SUH ITB-1 is a value of Ct = 0.75 and Cp = 1.4 by producing a peak discharge of 4.51 m³ / s, then optimization of the parameters at SUH ITB-2 is the value of Ct = 3 and Cp = 1.4 to produce a peak discharge of 8.42 m³ / s.